2019
DOI: 10.1016/j.toxrep.2019.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor-dependent induction of cripto-1 (one-eyed pinhead) inhibits zebrafish caudal fin regeneration

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…It plays an important role in the early embryonic development and the regeneration and differentiation of stem cells (Chambers et al, 2007;Bianco et al, 2009). There were few studies on Tgdf1 gene in fish, especially those related to pluripotency (Garland et al, 2019;Hoover et al, 2019). Our data showed that Oct4, Nanog, and Tgdf1 were characteristic genes to identify the pluripotency status of fish iPS-like cells.…”
Section: Discussionmentioning
confidence: 65%
“…It plays an important role in the early embryonic development and the regeneration and differentiation of stem cells (Chambers et al, 2007;Bianco et al, 2009). There were few studies on Tgdf1 gene in fish, especially those related to pluripotency (Garland et al, 2019;Hoover et al, 2019). Our data showed that Oct4, Nanog, and Tgdf1 were characteristic genes to identify the pluripotency status of fish iPS-like cells.…”
Section: Discussionmentioning
confidence: 65%
“…There is mounting evidence indicating that part of CRIPTO’s elusiveness involves its relegation to allostatic processes during injury and regeneration that can call it out from ‘hiding’. In zebrafish fin regeneration studies, CRIPTO was found to be induced by glucocorticoids, in a manner that is conserved in mammals, while retinoic acid (RA) inhibited CRIPTO induction in this setting [ 77 ]. In a mouse model of acute injury, secreted CRIPTO promotes myogenic commitment and differentiation, enhances early regeneration and reduces necrotic fibrotic areas [ 37 , 78 ].…”
Section: Rise and Fall Of Criptomentioning
confidence: 99%
“…Recombinant human NODAL triggered downstream SMAD2 phosphorylation in DU145 and LNCaP cells and attenuated AR signaling, suggesting that CRIPTO might mechanistically support the acquisition of a castration resistant phenotypes [ 151 ]. Paradoxically, in the zebrafish injury model, glucocorticoid receptor (GR) signaling induces CRIPTO expression but inhibits fin regeneration [ 77 ]. In cancer GR agonists are often tumor suppressive, likely because of downregulation of hormone signaling.…”
Section: Classical and Emerging Mechanisms Of Signalingmentioning
confidence: 99%
“…There is also evidence for vertebrate‐conserved SAR in GR signaling, which guides the development of novel GCs with the goal of preventing unwanted side effects (I. H. Song, Gold, Straub, Burmester, & Buttgereit, 2005). For example, some GCs like beclomethasone dipropionate increase expression of the feto‐oncogene Cripto‐1 / Tdgf1 in embryonic mouse cells, which could perturb several developmental pathways relevant to orofacial development (Garland et al, 2019). The development of GCs with lower risk for teratogenicity would be beneficial for pregnant women, especially for those who may unexpectedly require immunosuppression in emergency situations.…”
Section: Environmental Signaling Pathways In Orofacial Cleftsmentioning
confidence: 99%